Theoretical and applied aspects of the formation of ecological culture of schoolchildren in the process of physical education - Андрєєва, Олена; Головач, Інна; Хрипко, Інна (Slobozhanskyi Herald of Science and Sport, 2017)
Оlena Andrieieva, Inna Holovach & Inna Khrypko Purpose: scientifically substantiate and develop a program of classes using ecological tourism for primary school age children, aimed at the formation of ecological culture of schoolchildren. Material & Methods: pedagogical experiment was carried out in the form of ascertaining (191 schoolchildren: 96 boys, 95 girls) and formative (50 schoolchildren). The level of ecological culture of schoolchildren was assessed by the method of A. V. Asafova. The assessment of the level of physical health was carried out according to the method of G. L. Apanasenko. Results: model of ecological culture of schoolchildren of primary school age is theoretically grounded and developed, which includes the following components: axiological, motivational, activity, cognitive, and the basic criteria and levels of its formation in schoolchildren. The low level of ecological culture of schoolchildren is revealed. It is established that effective forms of ecological tourism are the ecological lesson, the ecological path, the ecological game, the ecological trip of the day off, the ecological excursion, the ecological camp. These funds were used to build a program of physical preparedness. Conclusion: positive influence of the developed program of ecological tourism on the indicators of physical condition, formation of ecological culture, organization of useful leisure and active recreation of children of primary school age.